ANALYSIS OF THE EFFECT OF THE X-RAY TUBE CURRENT ON UNIFORMITY IMAGE NOISE VALUES - Mberato, Anastasya Jessning Gamalita Mberato; Ratini, Ni Nyoman; Yuliara, I Made; Irhas, Rozi (Universitas Mataram, 2023)
This research aimed to evaluate the effects of the X-ray current tube on the uniformity value of CT image noise. This research used the CT images of Siemens head water phantom. The phantom was scanned with a Siemens Somatom Scope CT scanner for various current tubes (i.e., 180 mAs, 200 mAs, 220 mAs, 240 mAs, and 260 mAs) on tube voltage 110 kV, slice thickness 3 mm, and FOV 240 mm. The uniformity values in CT image noise were analyzed using the standard deviation value (SD). The SD was measured by the ROI process in 5 different locations, in the center and at 3 o'clock, 6 o'clock, 9 o'clock, and 12 o'clock on the images CT. Based on the result of a simple linear regression test using IBM SPSS ver 25, it was found that the current tube significantly affected the uniformity value of image noise (r2=0,9768, p<0,05). This result showed that increasing the current tube can reduce image noise uniformity. The highest image noise uniformity value was at a current at 180 mAs with 0,217 HU, and the lowest was at 260 mAs with 0,031 HU. This result also shows that all the values are less than 2 HU and still within the acceptable limit by the BAPETEN standard regulation.